2000
DOI: 10.1016/s0147-9571(99)00071-5
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus and concurrent infections with other enteropathogens in neonatal diarrheic dairy calves in Spain

Abstract: Faeces samples from 218, one to 30 days old, diarrheic dairy calves in 65 dairy herds were screened for the presence of rotavirus and concurrent infections with coronavirus, Cryptosporidium, F5+ Escherichia coli and Salmonella spp. Calves were grouped according to their age as follows: 1-7, 8-14, 15-21 and 22-30 days. Rotavirus infection was detected in 46.9%, 45.6%, 33.8% and 48.3% of the calves in the respective age-groups. No significant differences in the detection rate of rotavirus were found among calves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
56
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 14 publications
13
56
1
3
Order By: Relevance
“…E coli was the bacterial agent cultured with the highest frequency from diarrhoeic and healthy calves in our study, a finding that agrees with results of Bendali et al (1999a) and Garcia et al (2000). This study is the first to estimate the presence of virulence factors of Shiga toxin-producing Escherichia coli (STEC) from healthy and diarrhoeic calves and their relation with other enteropathogens in Austria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…E coli was the bacterial agent cultured with the highest frequency from diarrhoeic and healthy calves in our study, a finding that agrees with results of Bendali et al (1999a) and Garcia et al (2000). This study is the first to estimate the presence of virulence factors of Shiga toxin-producing Escherichia coli (STEC) from healthy and diarrhoeic calves and their relation with other enteropathogens in Austria.…”
Section: Discussionsupporting
confidence: 92%
“…In our study the coronavirus was detected in 40% of the diarrhoeic calves, which is a higher percentage in comparison with other studies (Bendali et al, 1999a;Garcia et al, 2000). Group A rotavirus identification in this survey (21.1%) is in agreement with Alfieri et al (2006), suggesting that the rotavirus is one of the more important causative agents in neonatal calf diarrhoea.…”
Section: Discussionsupporting
confidence: 64%
“…Nevertheless, concurrent shedding of BoTV with one or more enteropathogens was more commonly observed in calves Յ6 months old than in older cattle Ͼ6 months old, which is in agreement with previous reports indicating an increase in the probability of detection of multiple pathogens in calves. 6,12,28 Others have reported that mixed infections by enteropathogens were more commonly observed in diarrheic calves than in healthy ones, 28 which suggests that the presence of more than one enteropathogen may be one of the determining factors for clinical disease. A combined effect between BoTV and other enteric pathogens such as rotaviruses and astroviruses has been re- ported under experimental conditions, where concurrent infection with BoTV and either of the 2 viruses induced a more severe clinical disease than did each virus alone.…”
Section: Discussionmentioning
confidence: 99%
“…e patotipos de E. coli pode ter ocorrido, devido às condições ambientais favoráveis à manutenção de alta carga bacteriana, especialmente o alto índice pluviométri-co do período experimental, e a alta densidade de bezerros com faixa etária próxima. Estes resultados contrapõem os encontrados por García et al (2000) que relataram maior frequência da associação de Cryptosporidium spp. com Rotavírus.…”
Section: Quadro 2 Frequência (%) De Animais E Amostras Positivas Porunclassified